-2-x=-3x+6

Simple and best practice solution for -2-x=-3x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-x=-3x+6 equation:


Simplifying
-2 + -1x = -3x + 6

Reorder the terms:
-2 + -1x = 6 + -3x

Solving
-2 + -1x = 6 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-2 + -1x + 3x = 6 + -3x + 3x

Combine like terms: -1x + 3x = 2x
-2 + 2x = 6 + -3x + 3x

Combine like terms: -3x + 3x = 0
-2 + 2x = 6 + 0
-2 + 2x = 6

Add '2' to each side of the equation.
-2 + 2 + 2x = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 2x = 6 + 2
2x = 6 + 2

Combine like terms: 6 + 2 = 8
2x = 8

Divide each side by '2'.
x = 4

Simplifying
x = 4

See similar equations:

| 0.2(-0.87+7x)=1.9x | | -8(5-6n)=-424 | | 2/3x+15+17 | | (x-5)(x+11)=0 | | 6x-2(5)=50 | | 3(5x-6)+9=13x-7-2 | | 0x-4y=-20 | | 48x^5y^7+12x^4y^6+16x^4y=0 | | (x-10)(x)=0 | | 1+3(6b-3)=-134 | | (3/5)x=6 | | 13=-1/2y | | y=0.5+1 | | 5/(x+4)-6x/(3x+12)+7/(2x+8) | | 1/2m=35 | | .6x=1.5 | | 15x-9=13x-9 | | 8x-4(-7.5)=2 | | 6x-4y= | | 2p+3p-p=9-15-6 | | 180=(x+5)(x+1)x | | 6(0.15+w)=10 | | Z-4.6=-2.2-3z | | 8q-42=-26 | | -54=6z-18 | | 3/2(2x-2)1/5= | | 2(3t-6)=10t-t-6 | | 0.3+2.6=4.4 | | (275)(373-x)(.444)=(100)(x-295)(4.184) | | 3y+10=82 | | -1/7y^7*5/8y^2 | | 5m+25=-65 |

Equations solver categories